Standards project the future - Krechmer, Ken (Journal of Standardisation, 2023)
Standards are shown to be fundamental to measurements and measurements emerge with early agrarian civilizations. This paper proposes that each of the six human civilizations: hunter/gatherer, agrarian, city state, industrial, information, and the future, may be better understood by examining the general form of standards necessary for that civilization. Then the latest form of standards offers some insight into future value systems.